2022
DOI: 10.1130/ges02466.1
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale, crustal-block vertical extrusion between the Hines Creek and Denali faults coeval with slip localization on the Denali fault since ca. 45 Ma, Hayes Range, Alaska, USA

Abstract: Oblique convergence along strike-slip faults can lead to both distributed and localized deformation. How focused transpressive deformation is both localized and maintained along sub-vertical wrench structures to create high topography and deep exhumation warrants further investigation. The high peak region of the Hayes Range, central Alaska, USA, is bound by two lithospheric scale vertical faults: the Denali fault to the south and Hines Creek fault to the north. The high topography area has peaks over 4000 m a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 125 publications
0
18
0
Order By: Relevance
“…As the exception that proves the rule, the central segment of the Denali fault (cross-section C in Figure 3) lies south of the southern margin of thickening upper plate lithosphere. However, at this longitude, active deformation continues further north, both on the transpressive Hines Creek fault system and the Northern Foothills Thrust Belt, as inferred by Benowitz et al (2022) (Figures 1b and 3c), reaching the latitude where the upper plate thickens and mantle velocities increase to ∼4.5 km/s. Possible reductions in upper plate thickness associated with other major strike-slip faults also appear in the Vs model, for example, at the Kultag and Kobuk faults in cross-section A (Figure 3).…”
Section: Offsets In Lithospheric Thickness Across the Denali Faultmentioning
confidence: 77%
See 2 more Smart Citations
“…As the exception that proves the rule, the central segment of the Denali fault (cross-section C in Figure 3) lies south of the southern margin of thickening upper plate lithosphere. However, at this longitude, active deformation continues further north, both on the transpressive Hines Creek fault system and the Northern Foothills Thrust Belt, as inferred by Benowitz et al (2022) (Figures 1b and 3c), reaching the latitude where the upper plate thickens and mantle velocities increase to ∼4.5 km/s. Possible reductions in upper plate thickness associated with other major strike-slip faults also appear in the Vs model, for example, at the Kultag and Kobuk faults in cross-section A (Figure 3).…”
Section: Offsets In Lithospheric Thickness Across the Denali Faultmentioning
confidence: 77%
“…Numerical models of mantle deformation demonstrate the tendency for strain to localize at the margins of high viscosity mantle (Dayem et al., 2009; Molnar & Dayem, 2010). Localization of mantle deformation may be further enhanced by intrinsic weakness in the mantle of the Denali and Hines Creek fault systems, both of which are reactivated Mesozoic suture zones (Benowitz et al., 2022), by feedback mechanisms in which continued strain reduces mantle strength such as shear heating (Dayem et al., 2009; Regenauer‐Lieb et al., 2015; Willis et al., 2019) and/or damage rheologies (Bercovici & Ricard, 2012; Regenauer‐Lieb et al., 2015), or by the concentration of upward propagating magmas within the Denali and Hines Creek suture zones (Benowitz et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dextral strike-slip Denali Fault System in southern Alaska has long been the target of geophysical studies. With a well-documented 10-km northward thinning of the crust across the Denali Fault System and/or Hines Creek Fault (Figure 11b; Rossi et al, 2006;Veenstra et al, 2006;Brennan et al, 2011;Allam et al, 2017;Miller et al, 2018;Martin-Short et al, 2018;Haney et al, 2020;Mann et al, 2022;Gama et al, 2022aGama et al, , 2022b, the overall Denali Fault System acts as a major crustal boundary that separates the Alaska Range and the Wrangellia composite terrane to the south and the North American affinity terranes in the interior of Alaska to the north (W. Nokleberg et al, 2013;Benowitz et al, 2022). High-resolution finite-element models of Alaska that incorporated a Denali fault lithospheric shear zone (Jadamec et al, 2013;Haynie & Jadamec, 2017) found a better fit to surface motion and regions of exhumation and subsidence in south-central Alaska than models that did not include a Denali fault shear zone (Jadamec & Billen, 2010, 2012.…”
Section: The Velocity Model Clustering and Crustal Thickness Analyses...mentioning
confidence: 99%
“…This region is comprised of a series of amalgamated tectonic terranes (e.g., Silberling et al, 1994;Colpron et al, 2007;Moore & Box, 2016) and large-scale relict and active faults ; W. J. Nokleberg, Plafker, & Wilson, 1994;Plafker, Gilpin, & Lahr, 1994;Eberhart-Phillips et al, 2003;Benowitz et al, 2022) (Figure 1b). Some of the major fault systems in the study area include the Kobuk Fault Zone along the southern border of the Brooks Range in northern Alaska, the Kaltag and Tintina Faults in central Alaska, and the Denali Fault System in southcentral Alaska (Plafker, Gilpin, & Lahr, 1994).…”
Section: Introductionmentioning
confidence: 99%